Stres Kerja dan Burnout: Peran Mediasi Resilience pada Perawat di RSUD dr. Rasidin Padang - Renggani, Rinda; Zona, Mega Asri (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2024)
Purpose This study aims to examine: (1) The effect of job stress on burnout, (2) The effect of job stress on resilience, (3) The effect of resilience on burnout, and (4) The effect of job stress on burnout with resilience as a mediating variable. Methodology This research is a causal study that takes a population of 90 nurses in the inpatient room of RSUD Dr. Rasidin Padang with a total sampling method. Findings of the analysis showed that: (1) Job stress has a positive and significant influence on burnout in nurses at RSUD dr. Rasidin Padang, (2) Job stress has a negative and significant influence on resilience in nurses at RSUD dr. Rasidin, (3) Resilience has a negative and significant influence on burnout in nurses at RSUD dr. Rasidin Padang, and (4) Resilience mediates the effect of job stress on burnout.